Manajemen Perguruan Tinggi Pesantren - Mas'ud; Syaiful Alim (Ats-Tsaqofi: Jurnal Pendidikan dan Manajemen Islam, 2024)
Higher Education is education that is programmed after secondary school which includes diploma, bachelor, master, doctoral professors and specialist programs. pesantren is a learning resource center to explore religious knowledge. today many pesantren have established formal education.Islamic boarding schools have a distinctive and unique tradition compared to other educational institutions outside of pesantren. Islamic boarding schools have become a separate identity for Islamic educational institutions in Indonesia. pesantren not only give birth to ulama 'who are intellectual or vice versa, but also create ulama'-scientists and vice versa.The work of past scholars should be used as a support system to repeat the same achievements today. For this reason, we need today to realize academics that have Islamic boarding school values, because world civilization is starting to be torn apart because of us who began to move away from moral idealism.